2022
DOI: 10.2147/prbm.s389202
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Stereotypes on Trust in Doctors from Patients’ Perspective: The Mediating Role of Communication

et al.

Abstract: Purpose To investigate the relationship among patients’ stereotypes of doctors, effectiveness of doctors’ communication skills evaluated by patients, and patients’ trust in doctors. Patients and Methods A cross-sectional survey with a total of 3289 patients from 103 hospitals in eastern, central and western China was conducted. Results There were strong correlations among patients’ stereotypes, patients’ evaluation on doctors’ communication s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Consistent with the results of other studies that have found that physicians' professional skills and interpersonal communication skills are critical to building and maintaining patient trust. 32,33 In particular, physicians' respect for patient privacy have been shown to be key factors influencing patient trust. 34 These findings emphasize the dual role of the hospital environment and the individual physician's skills in improving the quality of healthcare delivery and patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the results of other studies that have found that physicians' professional skills and interpersonal communication skills are critical to building and maintaining patient trust. 32,33 In particular, physicians' respect for patient privacy have been shown to be key factors influencing patient trust. 34 These findings emphasize the dual role of the hospital environment and the individual physician's skills in improving the quality of healthcare delivery and patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 19 21 28 30 ] Thus, patients experiencing fear/anxiety related to healthcare procedures, regardless of type, may benefit from strategies and interventions designed to promote trust in medical professionals and develop positive relationships with them, which starts with promoting effective communication. [ 42 ]…”
Section: Discussionmentioning
confidence: 99%